Identification of a fluorometabolite from Streptomyces sp. MA37: (2R3S4S)-5-fluoro-2, 3, 4-trihydroxypentanoic acid. Issue 2 (11th December 2014) - Ma, Long; Bartholome, Axel; Tong, Ming Him; Qin, Zhiwei; Yu, Yi; Shepherd, Thomas; Kyeremeh, Kwaku; Deng, Hai; O'Hagan, David
Abstract : (2 R 3 S 4 S )-5-Fluoro-2, 3, 4-trihydroxypentanoic acid (5-FHPA) has been discovered as a new fluorometabolite in the soil bacterium Streptomyces sp. MA37. Abstract : (2 R 3 S 4 S )-5-Fluoro-2, 3, 4-trihydroxypentanoic acid (5-FHPA) has been discovered as a new fluorometabolite in the soil bacterium Streptomyces sp. MA37. Exogenous addition of 5-fluoro-5-deoxy-d -ribose (5-FDR) into the cell free extract of MA37 demonstrated that 5-FDR was an intermediate to a range of unidentified fluorometabolites, distinct from fluoroacetate (FAc) and 4-fluorothreonine (4-FT). Bioinformatics analysis allowed identification of a gene cluster ( fdr ), encoding a pathway to the biosynthesis of 5-FHPA. Over-expression and in vitro assay of FdrC indicated that FdrC is a NAD + dependent dehydrogenase responsible for oxidation of 5-FDR into 5-fluoro-5-deoxy-lactone, followed by hydrolysis to 5-FHPA. The identity of 5-FHPA in the fermentation broth was confirmed by synthesis of a reference compound and then co-correlation by 19 F-NMR and GC-MS analysis. The occurrence of 5-FHPA proves the existence of a new fluorometabolite pathway.